2016
DOI: 10.1111/jar.12307
|View full text |Cite
|
Sign up to set email alerts
|

Good Enough Support? Exploring the Attitudes, Knowledge and Experiences of Practitioners in Social Services and Child Welfare Working with Mothers with Intellectual Disability

Abstract: Workers in the area of social services and child welfare need access to training and professional development in the area of supporting mothers with intellectual disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…Practitioners, however, must balance promoting this right with the right that children have to be protected from harm. One way would be to adopt a preventative model that prioritizes early intervention, while acknowledging that support is likely to be required on a long-term basis, particularly at key points of transition (Collings et al, 2017;Stewart, MacIntyre, & McGregor, 2016;Stmadova et al, 2017). However, the resource implications of achieving this balance, particularly in times of austerity, are challenging as a result of the introduction of tighter eligibility criteria as a way to ration access to services (Lymberry, 2012).…”
Section: Discussion: Why Doe S In Con S Is Tent Pr Ac Ti Ce Contmentioning
confidence: 99%
See 1 more Smart Citation
“…Practitioners, however, must balance promoting this right with the right that children have to be protected from harm. One way would be to adopt a preventative model that prioritizes early intervention, while acknowledging that support is likely to be required on a long-term basis, particularly at key points of transition (Collings et al, 2017;Stewart, MacIntyre, & McGregor, 2016;Stmadova et al, 2017). However, the resource implications of achieving this balance, particularly in times of austerity, are challenging as a result of the introduction of tighter eligibility criteria as a way to ration access to services (Lymberry, 2012).…”
Section: Discussion: Why Doe S In Con S Is Tent Pr Ac Ti Ce Contmentioning
confidence: 99%
“…These include a lack of knowledge among professionals about the availability of appropriate services and supports for families (Sigurjonsdottir & Rice, 2017), but, importantly, also relate to assumptions made about the capacity of people with intellectual disabilities to parent, which often result in a crisis intervention model guided by risk (Booth & Booth, 2003;McConnell, Llewellyn, & Ferronato, 2002;Llewellyn, McConnell, Honey, Mayes, Russo, 2003). Stmadova, Bernoldova, Adamcikova, and Klusacek (2017), in a study of attitudes, knowledge and experiences of social welfare practitioners in the Czech Republic, found that most professionals held negative assumptions about the parenting capacity of parents with intellectual disabilities which then had a major impact on the support offered to them. Such attitudes suggest a presumption of incompetence, and McConnell et al (2002) argue that they promote a pessimistic approach that prevents workers from observing families' strengths and promoting family connections.…”
Section: Supp Orting Parents With Intellec Tual D Isab Ilitie S: Anmentioning
confidence: 99%
“…This study also found that, within the Bangladeshi community, people are expected to join a “cycle of life”, which includes marrying and having children. This allows people with intellectual disabilities to access socially valued roles (Edmonds, ) and is in contrast to findings of studies conducted with some White European family members and service staff, where the majority of participants express reservations about young people with intellectual disabilities getting married or having children (Aunos & Feldman, ; Strnadová, Bernoldová, Adamčíková, & Klusáček, ). It is hypothesized that basing descriptions of “intellectual disability” on everyday language, without a priori assumptions about what dis ability precludes, make marriage and parenting more accessible to people with intellectual disabilities.…”
Section: Discussionmentioning
confidence: 68%
“…The implication is that even when workers are willing, they may not be able to offer evidence‐based support to families headed by parents with intellectual disabilities and avert the need (should the need exist) for child apprehension. In this special issue, Strnadová, Bernoldová, Adamčíková, and Klusáček contribute to the literature on systems’ deficiencies, reporting findings from a national survey of child welfare and social services workers in the Czech Republic. Strnadová et al. report that while most workers held the view that women with intellectual disabilities could, under certain conditions, manage the mother role satisfactorily, most workers had limited knowledge of effective support strategies or available services that could assist these mothers.…”
Section: Research Impactmentioning
confidence: 99%